Possible association between eating behaviors and cardiovascular disease in the general population: Analysis of a nationwide epidemiological database. (March 2021) - Kaneko, Hidehiro; Itoh, Hidetaka; Kiriyama, Hiroyuki; Kamon, Tatsuya; Fujiu, Katsuhito; Morita, Kojiro; Michihata, Nobuaki; Jo, Taisuke; Takeda, Norifumi; Morita, Hiroyuki; Yasunaga, Hideo; Komuro, Issei
Abstract: Background and aims: Epidemiological evidence on the relationship between eating behaviors, including breakfast skipping, late night dinner, and bedtime snacking, and cardiovascular disease (CVD) events among the general population is scarce. We sought to explore the association of eating behaviors with subsequent CVD using a nationwide epidemiological database. Methods and results: Medical records of 1, 941, 125 individuals without prior history of CVD were extracted from the Japan Medical Data Center contracting with more than 60 insurers from multiple regions in Japan, mainly including employed working-age individuals. Skipping breakfast <3 times per week, late night dinner <3 times per week, and bedtime snacking <3 times per week were defined as optimal eating behaviors. Median age was 45 (interquartile range 39–53) years, and 1, 138, 676 were men. Median follow-up period was 978 (interquartile range 481–1790) days. Among them, 948, 805 individuals (48.9%) had optimal eating behaviors, whereas 647, 383 individuals (33.4%), 283, 017 individuals (14.6%), and 61, 920 individuals (3.2%) had single, double, and triple non-optimal eating behaviors, respectively. Individuals with non-optimal eating behaviors were younger and more likely to be men. Obesity and high waist circumference were more commonly observed in those with non-optimal eating behaviors. Multivariable Cox regression analysis showed that, compared with no non-optimal eating behavior, having non-optimal eating behaviors would have higher risk of myocardial infarction, angina pectoris, stroke, and heart failure. However, the dose-response relationship was not clear in the association between the number of non-optimal eating behaviors and incident CVD. Multivariable Cox regression analysis after multiple imputation for missing values also showed the association between non-optimal eating behaviors and incident CVD. Conclusions: Using a nationwide epidemiological database, we found a possible relationship between eating behaviors including skipping breakfast, late night dinner, and bedtime snacking, and subsequent cardiovascular events among the general population, suggesting the potential importance of maintaining optimal eating behaviors for the primordial and primary CVD prevention in the general population. Graphical abstract: Image 1 Highlights: Epidemiological evidence on the relationship between eating behaviors and cardiovascular disease (CVD) is scarce. We explored the association of eating behaviors with incident CVD using a nationwide epidemiological database. We focused on skipping breakfast, late night dinner, and bedtime snacking as non-optimal eating behaviors. We found a possible association between non-optimal eating behaviors and subsequent CVD. Our results suggest the importance of optimal eating behaviors for the primary CVD prevention.